Pelatihan Kapasitas SDM Bidang Pengelolaan Keuangan Pada Badan Usaha Milik Bersama (Bumdesma) - Supriono; Widiyohening, Caecilia Rosma (JCSE: Journal of Community Service and Empowerment, 2023)
BUMDesma exists as a "joint business", or as the parent of BUMDesma businesses in villages, where each unit, which stands independently, is regulated and managed in synergy by BUMDesma so that its business can grow and be empowered together. The problem that arises in BUMDesma is the limited human resources in the field of accounting, especially the process of preparing financial reports in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). The aim of this service activity is to help BUMDesma be able to present financial reports in accordance with accounting standards, which produces information for stakeholders quickly, accurately and accountably. The method used in this service is training and mentoring, this service activity is carried out in three stages. The results of this service activity are in the form of financial reports in accordance with SAK ETAP consisting of; balance sheet, income statement, statement of changes in equity, cash flow statement and notes to financial statements.